Hepatoprotective and Antioxidant Effects of Resveratrol Against Vincristine Sulfate Toxicity in Mice - Mahdi Vahidbalan; Mohammadreza Nasirzadeh (مجله دانشگاه علوم پزشکی گرگان, 2023)
Background and Objective: Vincristine is an important anticancer drug, which is highly toxic to the liver. It is a naturally occurring polyphenol found in many plants. Some studies have shown the anti-inflammatory and antioxidant effects of resveratrol. This study was conducted to determine the hepatoprotective and antioxidant effects of resveratrol against vincristine-induced toxicity in mice. Methods: In this experimental study, 32 female NMRI mice weighing 25-30 grams were randomly divided into four groups (n=8): control, vincristine, vincristine + resveratrol, and resveratrol. The animals received vincristine intraperitoneally at a dose of 3 mg/kg/bw once a week for four weeks. They also received resveratrol at a dose of 30 mg/kg for 28 days through gastric gavage. At the end of the study, the activity of alanine transaminase (ALT) and aspartate transaminase (AST) were measured. The level of antioxidant enzymes including superoxide dismutase (SOD), glutathione peroxidase (GPX), malondialdehyde (MDA) as well as total antioxidant capacity (TAC) was measured in the liver tissue of mice. Results: The activities of ALT, AST, SOD, and GPX decreased in the vincristine group compared to the control group, while MDA level increased significantly (P˂0.05). Treatment with resveratrol in the vincristine + resveratrol group improved the evaluated parameters compared to the vincristine group (P˂0.05). Conclusion: Resveratrol has protective and antioxidant effects against vincristine-induced oxidative damage in the liver of mice.